Psychological Factors on Teacher Education in Buddhist Sunday Schools in Lampung: I Ketut Damana - Damana, I Ketut (Acta Psychologia, 2024)
The aim of this research is to understand the psychological factors of teacher educators at the Lampung Buddhist Sunday School. The method used is a penomenological study, collecting data by finding data sources and recreating from various sources such as books, journals and existing research. The result is that psychological factors in teacher educators with research designs whose findings are not obtained from the form of calculations, but aim to reveal phenomenology in a holistic-contextual manner by collecting data from natural backgrounds and utilizing research as the key instrument. Research on psychological factors has a descriptive nature and tends to use an inductive analysis approach, so that processes and meanings based on the subject's perspective are more prominent in psychological factors, therefore psychological factors in meditation teachers in research are easy to understand by leaders and schools Buddhist week